Membrane Vesicles of Toxigenic Clostridioides difficile Affect the Metabolism of Liver HepG2 Cells - Estefanía Caballano-Infantes; Ailec Ho-Plágaro; Carlos López-Gómez; Flores Martín-Reyes; Francisca Rodríguez-Pacheco; Bernard Taminiau; Georges Daube; Lourdes Garrido-Sánchez; Guillermo Alcaín-Martínez; Raúl J. Andrade; Miren García-Cortés; M. Isabel Lucena; et al. (MDPI AG, 2023)
Clostridioides difficile infection (CDI) appears to be associated with different liver diseases. C. difficile secretes membrane vesicles (MVs), which may be involved in the development of nonalcoholic fatty liver disease (NALFD) and drug-induced liver injury (DILI). In this study, we investigated the presence of C. difficile-derived MVs in patients with and without CDI, and analyzed their effects on pathways related to NAFLD and DILI in HepG2 cells. Fecal extracellular vesicles from CDI patients showed an increase of Clostridioides MVs. C. difficile-derived MVs that were internalized by HepG2 cells. Toxigenic C. difficile-derived MVs decreased mitochondrial membrane potential and increased intracellular ROS compared to non-toxigenic C. difficile-derived MVs. In addition, toxigenic C. difficile-derived MVs upregulated the expression of genes related to mitochondrial fission (FIS1 and DRP1), antioxidant status (GPX1), apoptosis (CASP3), glycolysis (HK2, PDK1, LDHA and PKM2) and β-oxidation (CPT1A), as well as anti- and pro-inflammatory genes (IL-6 and IL-10). However, non-toxigenic C. difficile-derived MVs did not produce changes in the expression of these genes, except for CPT1A, which was also increased. In conclusion, the metabolic and mitochondrial changes produced by MVs obtained from toxigenic C. difficile present in CDI feces are common pathophysiological features observed in the NAFLD spectrum and DILI.